STUDY OF THE DIRECTION OF HINDUS IN MUGHAL INDIA - Singh, Ritesh Kumar; Parveen, Shagufta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The famous historian Sir Jadunath Sarkar says that "The criterion for testing the political system of any government is the effect it has on the economic and moral progress of the people during its rule." If we test the Mughal rule in India with this criterion, then we will have to say that it was a complete failure. During the short reign of Akbar, the economic and moral progress of the people was definitely made, but during the entire Mughal rule from 1556 to 1857 AD, the life of almost the entire Hindu population was miserable. From what the contemporary European traders and travelers and contemporary Muslim writers have written from time to time in this regard, it becomes clear that the Mughal rule was a curse for the Hindus and their life, their reputation and their property were not safe under the rule. In the words of historians, “The cause of all this destruction is Islamic fanaticism. When the rigid laws of Shariat are implemented to solve the complex problems of human government, then the unity and political equality of the people are destroyed and the people are forever divided into two parts. One of these parts is called Muslim and the other non-Muslim or Kafir.